Pengujian Black Box pada Aplikasi Ecommerce Berbasis Website Menggunakan Teknik Equivalence Partitions - Muhamad Ilham; David Apriansyah; Muhammad Rendy Nurhakiki; Novi Apriani; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Black box testing is testing based on the appearance (interface) and functionality of the software itself rather than the program source code. There are several methods of black box testing, one of which is equivalence partitioning, the method we use to test software. Equivalence Partitioning is a way to discuss whether an input is valid into the software and observe the accuracy of the input. That way you know what's missing from these features and what needs to be improved. Based on the results of the tests performed, it can be concluded that after fixing the bugs found, the software can be used normally. However, this test can be called imperfect because it is only performed on a few sample shapes. Based on the results of this test, it is expected that the application can be used according to user requirements.